CHEMICAL COMPOSITION, DIGESTIBILITY AND AEROBIC STABILITY OF CORN SILAGES HARVESTED AT DIFFERENT MATURITY STAGES - Silveira Rabelo, Carlos Henrique [UNESP]; De Rezende, Adauton Vilela; Silveira Rabelo, Flavio Henrique; Basso, Fernanda Carvalho [UNESP]; Haerter, Carla Joice [UNESP]; Reis, Ricardo Andrade [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
The objective of this study was to evaluate the effect of corn plant harvested in diferente maturity stages on the chemical composition, digestibility and aerobic stability of silages. The corn used in the study was the hybrid BM3061 harvested after 114, 121, 126, 133 and 140 days of sowing at five maturity stages based on the advancement of the grain milk line (early dent (ED), 1/3 of milk line (ML), 1/2 ML, 2/3 ML and black layer (BL)). A variation from 242.7 to 377.4 g of dry matter (DM) kg(-1) as fed was observed between the ED and BL stages; however, the measurements performed in this study did not exhibited major changes in the composition of these silages. The silages produced with plants that were harvested at the 1/2 ML, 2/3 ML and BL stages showed lower DM loss during the fermentative process. The silages produced with plants that were harvested at the ED and 1/3 ML stages showed higher in vitro organic matter digestibility (IVOMD) (0.584 and 0.631 g g(-1) of OM, respectively). The corn silages produced at the maturity stage of 2/3 ML showed a higher aerobic stability (104 hours) during the aerobic exposure. The 1/3 and 2/3 ML maturity stages seem to be the best harvest stages for the production of corn silage in tropical climates.
Keywords: Digestibility; Fermentation; Fiber; Tropical climate